ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA INTERAKTIF OBSERVARA BERBASIS GOOGLE SITES PADA PEMBELAJARAN MENULIS TEKS LAPORAN HASIL OBSERVASI - Jessica; Fabio Testy Ariance Loren; Andheska, Harry (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the needs analysis as the foundation for developing the Observara interactive media based on Google Sites in learning to write observation report texts for tenth-grade students. The study employed a Research and Development (R&D) approach using the Four-D (4D) model, with the discussion in this article limited to the Define stage. The Define stage consisted of front-end analysis, learner analysis, concept analysis, and specifying instructional objectives. Data were collected through interviews with an Indonesian language teacher, questionnaires administered to 32 tenth-grade students of SMA Negeri 4 Tanjungpinang, and document analysis. The findings revealed several learning problems, including students’ difficulties in generating ideas, organizing observation report texts according to the appropriate structure, and applying proper linguistic features. In addition, the learning media previously used had not optimally supported students’ understanding of the material. The learner analysis also indicated that students required more interactive learning media and showed positive readiness toward the use of Google Sites, supported by adequate digital facilities. Furthermore, the concept analysis and instructional objectives served as the basis for designing learning materials and activities that aligned with students’ needs. These findings demonstrate that the Define stage provides a comprehensive foundation for developing the Observara interactive media to support observation report text writing instruction.